BABC task scheduler: hybridisation of BAT and artificial bee colony for deadline constrained task scheduling. (2016) - Arunarani, A.R.; Manjula, D.
In information technology, one of the modern and rising trends is cloud computing, the foremost problems in cloud computing is task scheduling. A good scheduling algorithm has to reduce the execution time and cost together with QoS requirements of the users. In this paper, a task scheduling scheme with the aid of a hybridisation of BAT and artificial bee colony (BABC) on diverse computing systems is proposed. In BABC, each dimension of a solution represents a task and a solution as a whole signifies all tasks priorities. The vital issue is how to allocate users tasks to exploit the income of infrastructure as a service (IaaS) provider while promising quality-of-service (QoS). The generated solution is proficient to quality of service (QoS) and improves IaaS providers' credibility and economic benefit. According to the evolved results, it has been found that our algorithm always outperforms the traditional algorithms.